2021
DOI: 10.1016/j.eujim.2021.101323
|View full text |Cite
|
Sign up to set email alerts
|

The physical and mental health of the medical staff in Wuhan Huoshenshan Hospital during COVID-19 epidemic: A Structural Equation Modeling approach

Abstract: Introduction Early in the epidemic of corona virus disease 2019, the Chinese government recruited a proportion of healthcare workers to support the designated hospital (Huoshenshan Hospital) in Wuhan, China. The majority of front-line medical staff suffered from adverse effects, but their real health status during COVID-19 epidemic was still unknown. The aim of the study was to explore the latent relationship of the physical and mental health of front-line medical staff during this special period.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 49 publications
1
14
1
Order By: Relevance
“…In addition, it is worth mentioning that our results are in line with those of other authors who used structural equations models during the pandemic in other populations. Thus, they are consistent with the results of Wang et al, 2021 , which found a direct negative relationship of resilience to stress and anxiety in a sample of medical personnel in a hospital in Wuhan, Hubei Province's provincial capital (China)—the location of the first outbreak of COVID-19. They also support the results of Rodríguez-Hidalgo et al ( 2020 ), who showed a direct relationship between stress and anxious symptoms in university students throughout the COVID-19, again through a structural equation model.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, it is worth mentioning that our results are in line with those of other authors who used structural equations models during the pandemic in other populations. Thus, they are consistent with the results of Wang et al, 2021 , which found a direct negative relationship of resilience to stress and anxiety in a sample of medical personnel in a hospital in Wuhan, Hubei Province's provincial capital (China)—the location of the first outbreak of COVID-19. They also support the results of Rodríguez-Hidalgo et al ( 2020 ), who showed a direct relationship between stress and anxious symptoms in university students throughout the COVID-19, again through a structural equation model.…”
Section: Discussionsupporting
confidence: 91%
“…Resilience indeed represents an individual’s set of personal resources allowing them to optimally face stressors and difficulties (Fletcher & Sarkar, 2013 ; Newman, 2005 ). Thus, several investigations have discovered a negative association between resilience and anxiety during pregnancy (Lubián López et al, 2021 ), and between resilience towards stress and anxiety in other populations at the time of the pandemic (Braun-Lewensohn et al, 2021 ; Satici et al, 2020 : Wang et al, 2021 ). Additionally, previous researches carried out before the pandemic have proven the protective role of resilience regarding these variables in the perinatal stage (Armans et al, 2020 ; García-León et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The SRSS is a self-reported sleep quality measurement tailored for Chinese people (28). Its reliability and validity have been proven by several previous studies (29,30). The SRSS includes ten items with a score ranging from the best sleep quality (one point) to the worst sleep quality (five points).…”
Section: Assessment Of Sleep Qualitymentioning
confidence: 71%
“…The long-term exposure to medication procedures such as intubation and nebulization also leads to the high percentage of fatigue by fear of the hospital-acquired infections ( 16 , 17 ). Therefore, reducing the fatigue by tailored measures is critical to promote nurses' safety and health ( 18 ), and the environmental interventions could become a promising approach.…”
Section: Introductionmentioning
confidence: 99%